New Adaptive Starting Scalar Control Scheme for Induction Motor Variable Speed Drives - Travieso-Torres, J; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2022)
This article proposes a new scalar control scheme for variable speed drives of induction motors with an adaptive starting control. Besides centrifugal pumps, blowers, and fans, it expands the scalar control application field to move, for instance, a class of conveyor belts with nominal torque loading. An adaptive passivity-based controller designed for a class of nonlinear systems encompassing the dynamical machine model keeps a constant stator starting current. The proposed methodology uses information from the motor nameplate. Hence, it keeps a simple control scheme, not needing parameter estimates, neither adjusting controllers nor variable observers depending on them. Experimental results with a 10 HP downscaled laboratory prototype validate the proposed control strategy effectiveness. It shows rated-starting torque capabilities and fast speed response. Moreover, it shows lower stator current consumption than previous scalar control schemes. © 1986-2012 IEEE.